Analisis Efektivitas Pengobatan Herbal Komplementer Terhadap Kondisi Anemia Pada Kehamilan - Aulia Farah Azizah; Maslan Pangaribuan; Farida M Simanjuntak; Feri Setiadi (Jurnal Ayurveda Medistra, 2026)
Anemia during pregnancy is a condition in which hemoglobin levels decrease due to physiological demands, iron deficiency, and hemodilution throughout gestation. (Siregar, A. N. 2020) t remains a major maternal health concern because it increases the risk of preterm birth, postpartum hemorrhage, infection, and impaired fetal growth and development. This review aims to assess the effectiveness of complementary interventions using natural foods— particularly fruits and herbs rich in iron, folate, vitamin C, and antioxidants—in improving hemoglobin levels among pregnant women with anemia. Methods: The review includes several quantitative studies with quasi-experimental and one-group pre-posttest designs involving pregnant women in their second and third trimesters. Results indicated that consumption of dragon fruit, dates, moringa leaves, beetroot, honey, and black cumin increased mean Hb levels by 0.6–2.5 g/dL, with statistical significance at p ≤ 0.05. The accessible, and effective, making them a useful therapeutic option alongside iron supplementation. Integrating nutritional education and Hb monitoring for anemia during pregnancy offers additional synergistic benefits